(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, we will consider these epithets “kuunak/shayir // yrdap kongon/yr canduu”. These epithets form a single content framework and contain some information about the mentality and musical taste of the Kyrgyz people. For example, the epithets “kuunak” and “shayir” indicate that the Kyrgyz people are a cheerful, cheerful people who enjoy life and are openinded. On the other hand, the epithets “yrdap kongon” and “yr canduu” indicate that the Kyrgyz are a cheerful, singing people who are fond of singing and love to sing. This philological conclusion is confirmed by archaeological findings in petroglyphs belonging to the Kyrgyz people of the 19th century. More precisely, in the Batken (XVIII-XIX centuries) petroglyphs left by the Kyrgyz during these centuries, there is an image of a person putting an instrument in his mouth. In our opinion, this is a trumpet, a 30-40 cm long wooden wind musical instrument.